2021
DOI: 10.1111/asj.13600
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low and high levels of maternal nutrition consumed for the entirety of gestation on the development of muscle, adipose tissue, bone, and the organs of Wagyu cattle fetuses

Abstract: This study aimed to investigate the effects of high and low levels of energy intake during the entire gestation period on the skeletal muscle development, organ development, and adipose tissue accumulation in fetuses of Wagyu (Japanese Black) cows, a breed with highly marbled beef. Cows were allocated to a high-nutrition (n = 6) group (fed 120% of the nutritional requirement) or low-nutrition (n = 6) group (fed 60% of the nutritional requirement). The cows were artificially inseminated with semen from the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 46 publications
3
29
0
Order By: Relevance
“…Recently, we demonstrated that the skeletal muscle weight of fetuses of dams fed with 60% of crude protein (CP), crude fat (CF), and energy requirements was 1.27-to 1.72-fold lower than that of the fetuses of dams fed with 120% of the nutritional requirements [10]. The phenotypic alteration observed in this study promotes understanding the mechanism underlying the effect of MUN on muscle development and tissue metabolism in the fetuses.…”
Section: Introductionmentioning
confidence: 62%
See 4 more Smart Citations
“…Recently, we demonstrated that the skeletal muscle weight of fetuses of dams fed with 60% of crude protein (CP), crude fat (CF), and energy requirements was 1.27-to 1.72-fold lower than that of the fetuses of dams fed with 120% of the nutritional requirements [10]. The phenotypic alteration observed in this study promotes understanding the mechanism underlying the effect of MUN on muscle development and tissue metabolism in the fetuses.…”
Section: Introductionmentioning
confidence: 62%
“…In contrast to the effect on the myogenic process, the effect of MUN on metabolism of fetal skeletal muscle tissue remains poorly understood. The fetal skeletal muscle mass was reduced by MUN [10], possibly due to the retardation of whole process of skeletal muscle development. This could be a result of insufficient supply of energy and nutrient components that were required for the myogenic differentiation, muscle fiber maturation, and protein accumulation.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations